Study on the Efficiency of Fenton-SBR System in the Treatment of Fine Chemical Wastewater - XU Weidong; WEI Dongyang; LI Jie; ZHANG Fakui; ZHOU Wen (Renmin Zhujiang)
With characteristics of high pollutant concentration and difficult degradation,fine chemical wastewater is treated by Fenton-SBR system.In the test,response surface methodology is used to optimize Fenton pretreatment conditions to improve biodegradability.The effluent after Fenton pretreatment is introduced into SBR system for biochemical treatment,and sponge iron,volcanic rocks and polyurethane foam fillers are added into SBR system to improve treatment efficiency.The test results show that the optimal conditions for Fenton pretreatment of fine chemical wastewater by response surface methodology are as follows:initial pH is 4.10,H2O2 dosage is 9.11 mL/L,molar ratio of nH2O2 and nFe2+ is 12.31,reaction time is about 1 hour,and COD removal rate is 35.42%.The removal efficiency of COD,TN and TP by sponge iron SBR system can reach 31.83%,23.67% and 65.17% respectively.Kinetic analysis shows that the second-order kinetic equation can better reflect the degradation process of organic matter in SBR system.